Genetic characterization and molecular epidemiology of Coxsackievirus A12 from mainland China during 2010–2019 - Guo, Qin; Zhao, Hehe; Zhang, Yong; Wang, Xianjun; Yu, Qiuli; Tan, Zhaolin; Lu, Huanhuan; Xiao, Jinbo; Ji, Tianjiao; Zhu, Shuangli; Wang, Dongyan; Yang, Qian; et al. (Frontiers in Microbiology, 2022)
Coxsackievirus A12 (CVA12) is an enterovirus that has been isolated in many countries in recent years. However, studies on CVA12 are limited, and its effective population size, evolutionary dynamics and recombination patterns have not been clarified now. In this study, we described the phylogenetic characteristics of 16 CVA12 strains isolated from paediatric HFMD patients in mainland China from 2010 to 2019. Comparison of the nucleotide sequences and amino acid sequences with the CVA12 prototype strain revealed that the 16 CVA12 strains are identical in 78.8-79% and 94-94.2%, respectively. A phylodynamic analysis based on the 16 full-length VP1 sequences from this study and 21 sequences obtained from GenBank revealed a mean substitution rate of 6.61×10−3 substitutions/site/year (95% HPD: 5.16-8.20×10−3), dating the time to most recent common ancestor (tMRCA) of CVA12 back to 1946 (95% HPD: 1942-1947). The Bayesian skyline plot showed that the effective population size has experienced twice dynamic fluctuations since 2007. Phylogeographic analysis identified two significant migration pathways, indicating the existence of cross-provincial transmission of CVA12 in mainland China. Recombination analysis revealed two recombination patterns between 16 CVA12 strains and other EV-A, suggesting that there may be extensive genetic exchange between CVA12 and other enteroviruses. In summary, a total of 16 full-length CVA12 strains were reported in this study, providing valuable references for further studies of CVA12 worldwide.